2012
DOI: 10.1007/s00540-012-1336-3
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block reduces postoperative pain intensity and analgesic consumption in elective cesarean delivery under general anesthesia

Abstract: Two-sided TAP block with 0.25% bupivacaine in parturients who undergo cesarean section with a Pfannenstiel incision under general anesthesia can decrease postoperative pain and analgesic consumption. The time to the first analgesic rescue was longer in the parturients who received the TAP block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 21 publications
4
67
0
4
Order By: Relevance
“…In our study of a Control group and the QLB I group, the median of the total morphine dose administered subcutaneously in the first 24 hours was 20mg and 10mg respectively; and during the first 48 hours 30 mg and 15 mg respectively. This result compares with other authors' studies which evaluated morphine consumption by PCA iv during the first 24 hours, where performing the QLB II or TAPB had results of 7.5 mg, 18 mg, 19 mg and 25 mg across the different studies [14,21,22,26].…”
Section: Discussionsupporting
confidence: 47%
“…In our study of a Control group and the QLB I group, the median of the total morphine dose administered subcutaneously in the first 24 hours was 20mg and 10mg respectively; and during the first 48 hours 30 mg and 15 mg respectively. This result compares with other authors' studies which evaluated morphine consumption by PCA iv during the first 24 hours, where performing the QLB II or TAPB had results of 7.5 mg, 18 mg, 19 mg and 25 mg across the different studies [14,21,22,26].…”
Section: Discussionsupporting
confidence: 47%
“…All the studies reported the 24-hr pain score, and 11 trials documented the 24-hr morphine consumption. 22,24,27,29,34,35,44,46,47,56,57 Transversus abdominal plane block did not significantly reduce the pain score (Table 2) at 24 hr but significantly reduced the mean 24-hr opioid consumption by 10 mg (95% CI, -17.4 to -2.8; P = 0.006) compared with the control group ( Table 2). The US-guided and landmark subgroup analyses for Cesarean delivery studies are presented in Table 3.…”
Section: Transversus Abdominal Plane Block Vs Local Infiltrationmentioning
confidence: 94%
“…Another study conducted after cesarean delivery found that TAP group had reduced pain score and total morphine consumption in the first 48 postoperative hours [13]. The same promising results were also obtained on patients undergoing prostatectomy [7], appendectomy, cesarean section [16][17][18], colorectal resections [19] and total abdominal hysterectomy [14]. In contrary, the block does not provide additional benefit to multimodal analgesia in gynecological cancer surgery [20].…”
Section: Introductionmentioning
confidence: 85%
“…Accordingly, TAP block reduced the severity of postoperative pain in the first 24 postoperative hours by more than 70% as measured by VAS compared to the Non-TAPs. Studies conducted on patients undergoing abdominal surgery [6], total abdominal hysterectomy [14] and cesarean delivery showed a comparable reduction in the VAS of TAP group [13,17].…”
Section: /5mentioning
confidence: 94%